Improving Elementary Students’ Speaking Skills through Happy Holiday Activities Integrated with Islamic Values in Magelang City - Jendriadi, Jendriadi; Sariasih, Yanti; Susiyarni, Lina Sri (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study examines the effectiveness of the Happy Holiday program in enhancing elementary students’ speaking skills through engaging, value-based learning activities grounded in Islamic teachings. Speaking ability is a fundamental component of children’s communicative competence, yet many students in Magelang City continue to experience difficulties in expressing ideas confidently in public settings. Methodology: Using a qualitative descriptive design, the research involved 193 students from grades III–V across several schools, with data collected through participant observation, semi-structured interviews with students and parents, and documentation of learning activities. Thematic analysis revealed that the program successfully created an enjoyable, interactive, and low-pressure environment that improved students’ fluency, vocabulary mastery, clarity of expression, and willingness to speak. Main Findings: Activities such as storytelling about the Prophet’s companions, collaborative discussions, and Islamic-themed educational games not only enhanced students’ linguistic performance but also strengthened moral values such as honesty, responsibility, respect, and self-confidence. Integrating ethical character formation into speaking practice proved effective in fostering polite and meaningful communication. Novelty/Originality of this study: The novelty of this study lies in its development of a culturally rooted pedagogical model that merges non-formal learning, Islamic character education, and oral language development an approach rarely explored in Indonesian elementary education research. By demonstrating that holiday-based programs can reduce gadget dependency while enriching both communication skills and moral awareness, this study offers an innovative framework for alternative language learning initiatives that are contextually relevant, enjoyable, and character-oriented.